2021
DOI: 10.1111/aas.13813
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam versus dexamethasone‐ondansetron in preventing post‐operative nausea‐vomiting in patients undergoing laparoscopic surgeries

Abstract: Background: Midazolam reduces post-operative nausea and vomiting (PONV) when compared to a placebo or when used as an adjuvant to other antiemetics. The present study was designed to compare midazolam with a combination of dexamethasoneondansetron in preventing PONV.Methods: One hundred and twenty patients undergoing laparoscopic surgeries having 2 or more risk factors for PONV (simplified Apfel score) were randomised into 2 groups of 60 each. Patients in group D received 8-mg dexamethasone and 4-mg ondansetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Another study reported that administering midazolam 2 mg towards the end of surgery had an antiemetic effect similar to that of dual prophylaxis with IV dexamethasone 8 mg and IV ondansetron 4 mg. The PONV incidence within 24 h was 30% for the midazolam group and 33% for the dexamethasone and ondansetron group in patients undergoing laparoscopy, with an Apfel score ≥2, which was similar to the findings of our study [ 28 ]. Midazolam was also effective when used as a combination therapy with other classes of antiemetics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another study reported that administering midazolam 2 mg towards the end of surgery had an antiemetic effect similar to that of dual prophylaxis with IV dexamethasone 8 mg and IV ondansetron 4 mg. The PONV incidence within 24 h was 30% for the midazolam group and 33% for the dexamethasone and ondansetron group in patients undergoing laparoscopy, with an Apfel score ≥2, which was similar to the findings of our study [ 28 ]. Midazolam was also effective when used as a combination therapy with other classes of antiemetics.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the antiemetic effect of midazolam may result from the activation of different receptors when compared with other antiemetics such as ondansetron or dexamethasone. As in the aforementioned studies, the frequently used midazolam doses for PONV were 2 mg or 0.04–0.075 mg/kg [ 12 , 13 , 26 , 27 , 28 ]. Grant et al [ 10 ] showed similar effects between lower (<0.05 mg/kg) and higher doses (≥0.075 mg/kg) for preventing PONV, and we decided to use midazolam 0.05 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Prakash et al [ 16 ] reported that midazolam may reduce the incidence of PONV by inhibiting the chemoreceptor trigger zone activity and reducing the release of 5-hydroxy tryptamine (5-HT) by binding to the gamma-aminobutyric acid (GABA) receptor. However, since remimazolam is rapidly metabolized by carboxylesterase, the context-sensitive half-time (CSHT) is 7–8 min for a 2-hour continuous infusion, which is similar to that of propofol and much shorter than that of midazolam [ 17 ].…”
Section: Discussionmentioning
confidence: 99%